Introducing a quality variable in the theory of product differentiation: Abbott (1953) and Dorfman and Steiner (1954) - Julien Gradoz (Duke University, Center for the History of Political Economy (CHOPE), 2024)
We trace the origins of the definition of the "quality variable" used in the theory of product differentiation, which states that quality is unanimously appreciated by consumers, entails a higher unit cost for firms, is unidimensional and continuous. We also document the transition from a diagrammatic treatment of the issue of product quality to an algebraic one in this theory. To do so, we examine two articles published a year apart in the American Economic Review: an article written by Lawrence Abbott (1953) and an article written by Robert Dorfman and Peter Otto Steiner (1954).
Keywords: B21; D40; 330; Quality Variable; Product Differentiation; Lawrence Abbott; Robert Dorfman; Peter Otto Steiner